An Economic Sociology of Law Reimagined Beyond Embeddedness (Taylor & Francis, 2023)
Sociology of law
English
Keywords: Commercial law; Company, commercial & competition law; Economic theory & philosophy; Jurisprudence & general issues; Sociology of law